Écritures impossibles : du Livre mallarméen au Hors-Livre de Derrida - Giorgia Testa (Revue Italienne d'Etudes Françaises, 2023)
This article aims to establish the link between the notion of Livre in Stéphane Mallarmé’s work and that of Hors-Livre in Jacques Derrida’s œuvre, by highlighting the profound influence that the poet’s work had on the Derridian philosophy as far as the “literary object” is concerned. Starting with the Coup de dés, this article traces the filiation between Mallarmé’s poems and the writing of La double séance, in order to show how deconstruction appropriates the marks of the poet of the rue de Rome, digging them up and exasperating them.